Fluoride Knowledge, Attitudes, and Behaviors: Adults in Rural Alabama - Alex Harper; Steven M. Levy; Wei Shi (Journal of Primary Care & Community Health)
Introduction: Despite strong evidence supporting the benefits of water fluoridation in preventing dental caries, limited research exists on U.S. adults’ knowledge, attitudes, and behaviors regarding fluoride and tap water intake. This study examined the knowledge, attitudes, and behaviors regarding fluoride and tap water intake of Green Hill, Alabama adults. Methods: A convenience sample of 291 adults was surveyed concerning their knowledge, attitudes, and behaviors about fluoride in water and toothpaste, and water consumption preferences. Results: There was a high level of knowledge about fluoride’s role in cavity prevention, with 92.4% correctly identifying its benefits. However, 18.3% were unaware that fluoride does not help maintain healthy gums. Regarding attitudes, 14.5% strongly agreed and 28.3% agreed that fluoride in drinking water was beneficial, while 29.1% strongly supported and 53.5% supported its inclusion in toothpaste. A preference for bottled water over tap water was noted by 84.4% of participants, with 36.9% citing distrust of tap water quality as a primary reason. Bivariate analysis found a positive perception of fluoride in tap water correlated with better knowledge, while education level and fluoride awareness influenced attitudes. Conclusion: Additional research is necessary to explore reasons underlying adults’ water consumption habits and fluoride perceptions.